Enabling innovative healthcare delivery through the use of the focused factory model: the case of the spine clinic of the future. (3rd February 2005) - Wickramasinghe, N.; Bloemendal, J.W.; De Bruin, A.K.; Krabbendam, J.J.
This paper discusses the concept of the focused factory model. We highlight that the focused factory model combines one of the key generic strategies identified by Michael Porter (1985) and the ideas and concepts from manufacturing. The genesis of this model has its roots in trying to restore the competitive edge for manufacturing in the US. We assert that this model has much benefit for healthcare and, by applying such a model to the structuring of healthcare facilities, we can realise the benefits of this model that have been experienced in manufacturing; namely, we can achieve a competitive edge to healthcare delivery. We illustrate our ideas by presenting the design for a new Spine Clinic in the Netherlands.